2018
DOI: 10.13057/biodiv/d190603
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of Siganus fuscescens across urban reefs of Seribu Islands, Northern of Jakarta, Indonesia

Abstract: Bramandito A, Subhan B, Prartono T, Anggraini NP, Januar HI, Madduppa HH. 2018. Genetic diversity and population structure of Siganus fuscescens across urban reefs of Seribu Islands, Northern of Jakarta, Indonesia. Biodiversitas 19: 1993-2002. Jakarta bay and Seribu Islands reefs have been affected by anthropogenic activities which causing them degraded and low quality of the ecosystem. However, lack of study has been conducted to investigate the effect on reef fish population due to change in ecosystem qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…The idea that dispersal characteristics may have influenced the difference in population structure in S. rivulatus and S. diaspros is also consistent with previous studies that have shown some evidence of structure in Stephanolepis filefishes (Yoon et al 2012), and a lack of structure in Mediterranean rabbitfishes (Bonhomme et al 2003;Hassan et al 2003;Hassan and Bonhomme 2005;Azzurro et al 2006). It is important to note, however, that other species of Pacific rabbitfishes, do show some, albeit low, levels of population structure in Indonesia and in Guam (Priest et al 2012;Bramandito et al 2018).…”
Section: Dispersal Mechanismssupporting
confidence: 85%
“…The idea that dispersal characteristics may have influenced the difference in population structure in S. rivulatus and S. diaspros is also consistent with previous studies that have shown some evidence of structure in Stephanolepis filefishes (Yoon et al 2012), and a lack of structure in Mediterranean rabbitfishes (Bonhomme et al 2003;Hassan et al 2003;Hassan and Bonhomme 2005;Azzurro et al 2006). It is important to note, however, that other species of Pacific rabbitfishes, do show some, albeit low, levels of population structure in Indonesia and in Guam (Priest et al 2012;Bramandito et al 2018).…”
Section: Dispersal Mechanismssupporting
confidence: 85%
“…and transferred to the laboratory for further analysis. The fish samples obtained had an average weight of 59.87 ± 28.26 g and an average length of 14.95 ± 2.26 cm [19].…”
Section: Sample Collectionmentioning
confidence: 99%
“…The primer used was COI 501F 5'CATGAAACCTCCYGCTATYTCC3 'COI 1286R 5'TGTTGTGGGAAGAAAGTYAGRTT3'. The PCR process was carried out for 35 cycles, each cycle consisting of initial denaturation at 94⁰C for 30 seconds, annealing cycle at 52⁰C for 35 seconds and extension at 70⁰C for one minute [19].…”
Section: Dna Amplification (Pcr)mentioning
confidence: 99%
“…Pie depicts the relative percentage of each category structure in Stephanolepis filefishes (Yoon et al 2012), and a lack of structure in Mediterranean rabbitfishes (Bonhomme et al 2003;Hassan et al 2003;Hassan and Bonhomme 2005;Azzurro et al 2006). It is important to note, however, that other species of Pacific rabbitfishes, do show some, albeit low, levels of population structure in Indonesia and in Guam (Priest et al 2012;Bramandito et al 2018).…”
Section: Dispersal Mechanismsmentioning
confidence: 99%